Rett Syndrome as a movement and motor disorder – A narrative review. (September 2020) - Brunetti, Sara; Lumsden, Daniel E.
Abstract: Rett syndrome (RTT) is neurodevelopmental disorder affecting approximately 1:10000–15000 live female births, commonly associated with MECP2 gene mutations. Hand stereotypies and gait disturbance, as well as spasticity and dystonia, were noted in RTT since first descriptions. This review aimed to explore the prevalence of reported movement disorders in RTT. Data sources and extraction: Pubmed and Embase databases for papers describing features of movement disorders in RTT. Papers were selected if included description of case report, cohort or case-series of patients with RTT including descriptions of clinical features of their movement disorder. Papers were divided into 3 epochs – i) Pre-1999, ii) 2000–2009, and iii) 2010 onwards. Results: 32 studies (13 in the first, 10 in the second and 9 in the third epochs) reported on movement disorders in RTT. Hand stereotypies were almost universal, diminishing but not disappearing over time. Gait disturbance and ataxia/tremor were also very common (>50% cases). Hypertonia was also often reported, increasing with age. In earlier descriptions spasticity was commonly described, with greater reference to dystonia/rigidity in more recent reports. Myoclonus and choreoathetosis were uncommonly reported. Conclusions: Movement disorders beyond hand stereotypies are common in RTT, most notably tremor. Hypertonia is frequently seen in RTT, increasing in prevalence with age, with apparent changes in nomenclature over time, (i.e early epoch spasticity, late epoch dystonia). Dystonia was specifically reported in 229/417 cases. Further work is required to explore the relative contribution of dystonia and rigidity to hypertonia in RTT, as well as the impact of these impairments when present. Highlights: Hand stereotypies are almost universal in Rett syndrome. Gait disturbance, ataxia and tremor are also common movement disorders in RTT. Elements of hypertonia are very common in RTT, increasing with age. Earlier descriptions mostly described spasticity, recent reports dystonia/rigidity. Further studies are required to determine what is causing elevated tone in RTT.